2018
DOI: 10.1002/nbm.3932
|View full text |Cite
|
Sign up to set email alerts
|

Breast magnetic resonance elastography: a review of clinical work and future perspectives

Abstract: This review on magnetic resonance elastography (MRE) of the breast provides an overview of available literature and describes current developments in the field of breast MRE, including new transducer technology for data acquisition and multi-frequency-derived power-law behaviour of tissue. Moreover, we discuss the future potential of breast MRE, which goes beyond its original application as an additional tool in differentiating benign from malignant breast lesions. These areas of ongoing and future research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
(185 reference statements)
0
24
0
Order By: Relevance
“…MR elastography yields quantitative images, and therefore imaging biomarkers, that map the absolute value of the complex shear modulus G Ã in terms of its two components, the elasticity modulus G d (a measure of the ability of an object to resume a normal shape after being stretched or compressed) and the viscosity modulus G l (a measure of resistance to gradual deformation by shear or tensile stress). We and others have demonstrated, in preclinical tumor models and cancer patients in vivo, the potential of the MR elastography-derived mechanical phenotype to inform on the underlying tumor microstructure and treatmentinduced changes to its integrity (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…MR elastography yields quantitative images, and therefore imaging biomarkers, that map the absolute value of the complex shear modulus G Ã in terms of its two components, the elasticity modulus G d (a measure of the ability of an object to resume a normal shape after being stretched or compressed) and the viscosity modulus G l (a measure of resistance to gradual deformation by shear or tensile stress). We and others have demonstrated, in preclinical tumor models and cancer patients in vivo, the potential of the MR elastography-derived mechanical phenotype to inform on the underlying tumor microstructure and treatmentinduced changes to its integrity (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The role of MRE in the evaluation of malignant tumors in various cancers including breast cancer has been reported . Recently Bohte et al have reviewed the potential of breast MRE . Lorenzen et al have reported changes in the elasticity of breast tissue as a function of the menstrual cycle .…”
Section: Mri‐related Methods In the Study Of Breast Cancer Metabolismmentioning
confidence: 99%
“…Magnetic resonance elastography has been proven successful and robust in a broad range of applications, from clinical diagnosis of liver diseases [386] to brain [280], and breast [387] pathologies. However, generalization of MRE in clinics is impacted by the scan time required for the acquisition of complete data sets necessary for accurate reconstruction.…”
Section: Magnetic Resonance Shear Wave Elastographymentioning
confidence: 99%